TNF-308 G/A polymorphism and risk of systemic lupus erythematosus in the Polish population. Issue 5 (September 2015) - Piotrowski, Piotr; Wudarski, Mariusz; Sowińska, Anna; Olesińska, Marzena; Jagodziński, Paweł P.
Abstract Objectives. Numerous studies have been performed with TNF-α-308 G/A (rs1800629) single nuclear polymorphism (SNP) to evaluate the risk of SLE in various ethnicities. However, the significance of TNF-α-308 G/A in both clinical and laboratory studies of the disease remains unclear. Methods. Using a high-resolution melting curve analysis, we assessed the prevalence of TNF-α-308 G/A SNP in SLE patients (n = 262) and controls (n = 528) in a Polish population. We also assessed the contribution of this SNP to various clinical symptoms and the presence of autoantibodies in SLE patients. Results. The p-value obtained using a χ2 test for the trend of TNF-α-308 G/A was statistically significant (ptrend = 0.0297). However, using logistic regression analysis for the presence of the HLA-DRB1*03:01 haplotype, we observed that the TNF-α-308 G/A SNP may be the DRB1*03:01-dependent risk factor of SLE in the Polish population. There was a significant contribution of TNF-α-308 A/A and A/G genotypes to arthritis OR = [2.692 (1.503–4.822, p = 0.0007, pcorr = 0.0119)] as well as renal SLE manifestation OR = [2.632 (1.575–4.397, p = 0.0002, pcorr = 0.0034)]. There was a significant association between TNF-α-308 A/A and A/G genotypes and the presence of anti-Ro antibodies (Ab) OR = 3.375(1.711–6.658, p = 0.0003, pcorr = 0.0051). However, the logistic regression analysis revealed that only renal manifestations and the presence of anti-anti-Ro antibodies remained significant after adjustment to the presence of the HLA-DRB1*03:01 haplotype. Conclusion. Our studies indicate that the TNF-α-308 G/A polymorphism may be a DRB1*03:01 haplotype-dependent genetic risk factor for SLE. However, this SNP was independently associated with renal manifestations and production of anti-Ro Ab.